2019
DOI: 10.1029/2018jd029668
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for a Record‐Breaking Rainfall in the Coastal Metropolitan City of Guangzhou, China: Observation Analysis and Nested Very Large Eddy Simulation With the WRF Model

Abstract: Record‐breaking rainfall of 524.1 mm in 24 hr occurred in the coastal metropolitan city of Guangzhou, China, during 6–7 May 2017 and caused devastating flooding. Observation analysis and a nested very large eddy simulation (VLES) with Weather Research and Forecasting (WRF) model were conducted to investigate various factors that contributed to the heavy rainfall, including synoptic weather pattern, topographic effects, cold pool, and urban effects. First, the warm and moist southerly flow in the lower troposph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 57 publications
8
56
0
1
Order By: Relevance
“…The ACCB was the main force for supporting the development and maintenance of updrafts, corresponding to the warm anomaly areas of perturbation potential temperature (Figure a). This result is consistent with that of Huang, Liu, et al (), who showed that high convective available potential energy (CAPE) was persistently observed in this region. The existence of abundant moisture in the lower troposphere (mentioned in section ) and the latent heat removed in the upper troposphere (discussed in section ) were important to maintain the total buoyancy.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The ACCB was the main force for supporting the development and maintenance of updrafts, corresponding to the warm anomaly areas of perturbation potential temperature (Figure a). This result is consistent with that of Huang, Liu, et al (), who showed that high convective available potential energy (CAPE) was persistently observed in this region. The existence of abundant moisture in the lower troposphere (mentioned in section ) and the latent heat removed in the upper troposphere (discussed in section ) were important to maintain the total buoyancy.…”
Section: Resultssupporting
confidence: 93%
“…Both positive and negative total potential temperature tendencies existed in the warm anomaly (Figure a), but their values were an order of magnitude smaller than those of latent heating and advection cooling. Therefore, the cooling from advection in the upper troposphere helped maintain the CAPE of the rising parcels that originated in the lower troposphere, which is consistent with the large CAPE generation rate attributable to the large‐scale advection shown by Huang, Liu, et al (). This process was crucial for the persistent development of updrafts.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations